Is Hell the Other?: Kierkegaard and Sartre on the Dialectic of Recognition - Söderquist, K. Brian (Kierkegaard studies. Yearbook, 2021)
This study asks how Sartre's version of the dialectic of recognition is present in Kierkegaard's works. For Sartre, the dialectic begins with an awareness that the other sees me and judges me. I experience this as a threat to my autonomy, and I fight back with a variety of strategies designed to mitigate the effects. Inter-subjective relationships are grounded in conflict from which there is no exit. Similarly, Kierkegaard characterizes the natural, self-centered way of seeing the other as inherently self-centered and contentious. And yet some of Kierkegaard's texts lay the ground for a way out. Unlike Sartre, he is sensitive to modifications to the structure of the dialectic of recognition that depend on a change in the basic mode of looking. That is, how I see, evaluate, and judge the other can alter the foundation of the interaction from something mutually contentious to something mutually edifying.